Detection of a novel herpesvirus associated with squamous cell carcinoma in a free-ranging Blanding's turtle. (March 2021) - Andersson, Kirsten E.; Adamovicz, Laura; Mumm, Lauren E.; Winter, John M.; Glowacki, Gary; Teixeira-Neto, Rachel; Adkesson, Michael J.; Hostnik, Eric T.; Haynes, Ellen; Allender, Matthew C.
The spread of both infectious and noninfectious diseases through wildlife populations is of increasing concern. Neoplastic diseases are rarely associated with population-level impacts in wildlife; however, impacts on individual health can be severe and might reflect deteriorating environmental conditions. An adult male free-ranging Blanding's turtle ( Emydoidea blandingii ) originally captured in 2005 and deemed healthy, was recaptured in 2018 with a 1 × 1.5 cm intra-oral broad-based right mandibular mass. An excisional biopsy was performed, and histopathology revealed squamous cell carcinoma (SCC). Consensus herpesvirus PCR identified a novel herpesvirus (proposed name Emydoidea herpesvirus 2 [EBHV-2]) within the tumor. EBHV-2 shares 85% sequence homology with Terrapene herpesvirus 2 (TerHV-2), a herpesvirus linked to fibropapillomas in eastern box turtles ( Terrapene carolina carolina ). Virus-associated fibropapillomas have been identified in multiple marine turtle species and have had debilitating effects on their populations, but to date, virus-associated SCCs are rarely reported.